MRI activity in MS and completed pregnancy: Data from a tertiary academic center. Issue 6 (5th November 2020) - Houtchens, Maria; Bove, Riley; Healy, Brian; Houtchens, Stepan; Kaplan, Tamara Bockow; Mahlanza, Tatenda; Chitnis, Tanuja; Bakshi, Rohit
Abstract : Objective: To evaluate postpartum MRI activity in patients with MS and a completed pregnancy and to compare these results to an age-matched untreated nonpregnant MS cohort. Methods: Patient with MS from a tertiary care MS center between 2006 and 2015, with prepartum and postpartum neurologic follow-ups and MRI scans were analyzed. Clinical activity and inflammatory brain MRI activity (new T2-hyperintense or gadolinium-enhancing [Gd+] lesions) were assessed peripartum. The results were compared with untreated reproductive-age patients with MS from the placebo arm of the clinical trials. Results: A total of 123 pregnancies in 123 women (median Expanded Disability Status Scale 1.0) were analyzed. Approximately 7.2% relapsed during pregnancy and 48.7% relapsed postpartum. Of pregnancies with prepartum and postpartum gadolinium (Gd)-enhanced MRI (n = 112), 8% had Gd+ lesions prepartum and 33% had new Gd+ lesions postpartum. Overall, 54.4% had either new T2 or Gd+ lesions postpartum. Seventy-nine percent of subjects with postpartum relapse had new MRI activity compared with 37.1% without relapse ( p < 0.001). Twenty-five percent had both clinical and radiographic activity and only 24.9% maintained no evidence of disease activity status postpartum. There was no association between postpartum MRI activity and disease-modifying treatments (DMTs) ( p > 0.5). MRI and clinical outcomes were also assessed for 126 nonpregnant untreated female patients with MS. Comparing pregnancy and no pregnancy groups, there was no difference in MRI activity at follow-up. Conclusions: There was a high level of inflammatory radiographic disease activity which was related to relapses in postpartum patients with MS. Further studies are needed to determine whether hormonal fluctuations vs extended time off DMTs may be the underlying cause of our observations.